Surrounding habitats mediate the trade-off between land-sharing and land-sparing agriculture in the tropics - Gilroy, James J.; Edwards, Felicity A.; Uribe, Claudia A. Medina; Haugaasen, Torbjørn; Edwards, David P. (The Journal of applied ecology, 2014)
1. Two strategies are often promoted to mitigate the effects of agricultural expansion on biodiversity: one integrates wildlife-friendly habitats within farmland (land sharing), and the other intensifies farming to allow the offset of natural reserves (land sparing). Their relative merits for biodiversity protection have been subject to much debate, but no previous study has examined whether trade-offs between the two strategies depend on the proximity of farmed areas to large tracts of natural habitat. 2. We sampled birds and dung beetles across contiguous forests and agricultural landscapes (low-intensity cattle farming) in a threatened hotspot of endemism: the Colombian Chocó-Andes. We test the hypothesis that the relative biodiversity benefits of either strategy depend partially on the degree to which farmlands are isolated from large contiguous blocks of forest. 3. We show that distance from forest mediates the occurrence of many species within farmland. For the majority of species, occurrence on farmland depends on both isolation from forest and the proportionate cover of small-scale wildlife-friendly habitats within the farm landscape, with both variables having a similar overall magnitude of effect on occurrence probabilities. 4. Simulations suggest that the biodiversity benefits of land sharing decline significantly with increasing distance from forest, but land sparing benefits remain consistent. In farm management units situated close to large contiguous forest (<500 m), land sharing is predicted to provide equal benefits to land sparing, but land sparing becomes increasingly superior in management units situated further from forest (1500 m). The predicted biodiversity benefits of land sparing are similar across all distances, provided that sparing mechanisms genuinely deliver protection for contiguous forest tracts. 5. Synthesis and applications. The persistence of bird and dung beetle communities in low-intensity pastoral agriculture is strongly linked to the proximity of surrounding contiguous forests. Land-sharing policies that promote the integration of small-scale wildlife-friendly habitats might be of limited benefit without simultaneous measures to protect larger blocks of natural habitat, which could be achieved via land-sparing practices. Policymakers should carefully consider the extent and distribution of remaining contiguous natural habitats when designing agri-environment schemes in the tropics.